Aspectos da farmacocinética do tacrolimus nos quatro primeiros dias após o transplante de fígado: contribuição para o ajuste da dose - Luiz Fernando Veloso (2006)
The aim of the present study is to describe the pharmacokinetic behavior of tacrolimus during the first four days after liver transplantation and to contribute to the establishment of an objective method for dose adjustment. In a prospective self-paired study, the residual blood concentration of tacrolimus and its relationship with the administered dose were analyzed in 203 adult recipients of whole liver grafts during the first four days after transplantation. An objective strategy for the definition of dose adjustment based on blood concentration was established. A progressive increase in blood tacrolimus concentration was observed during the first 60 hours of drug use. Thereafter, stabilization of the ratiobetween the concentration obtained and the dose administered was observed. Linear regression showed a 1.862-, 1.477- and 1.080-fold variation in the concentration/dose ratio at 24 hours after the first, second and third dose, respectively. The variation in this ratio showed good linearity over time, mainly after the second dose (Pearsons R2: 0.809 to0.851). After three subsequent dose adjustments using the traditional method, the proportion of patients with adequate blood concentrations of the drug remained unchanged (43.3% versus 60.8%, p=0.758). In conclusion, we found that the method of daily measurements of residual concentration is insufficient to prevent the occurrence of inadequate tacrolimus levels, at least when the subsequent dose adjustment is performed empirically. Dose adjustment should take into account the tendency toward an increase in blood concentration of the drug during the first 60 hours, in order to prevent elevated blood levels of the drug on subsequent days. The following equation is suggested for the estimation of the necessary dose: dose = target concentration / [(current concentration / vesperal dose) * A], where A corresponds to the expected variation in the concentration/dose ratio according to the number of doses of the drug administered until the time considered for adjustment (1 dose = 1.862, 2 doses = 1.477, 3 doses = 1.080).